Analisis Pemahaman Mahasiswa terhadap Konsep Efek Fotolistrik pada Mata Kuliah Fisika Kuantum: Analysis of Student Understanding of the Concept of the Photoelectric Effect in Quantum Physics Courses - Putri Anastasya; Sentia Situmorang; Trisna Herawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to understand students' understanding of the concept of the photoelectric effect in the Quantum Physics course. Data collection was carried out through a questionnaire on a scale of 1-5 to measure the level of students' understanding of the main aspects of the photoelectric effect, such as the role of photons, the relationship between light wavelength and photon energy, as well as imposing this phenomenon on the development of applicable mechanical theory. The results of the analysis show that the majority of students have a fairly good level of understanding, especially in the basic concept of the photoelectric effect as evidence of the dual nature of light. However, there is a harmony of understanding on experimental and applicable aspects, such as laboratory procedures and the relevance of photoelectric effect technology. These findings provide important insights for the refinement of teaching methods and emphasis on practical applications to improve students' understanding of these quantum phenomena.